Teaching Reading online For a Small Class: An Instructional Design for Teaching Reading Online - Yopi Arianto (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2020)
The digital technology has equipped people especially the students with applications needed for online learning in the form of applications. However, these applications will be useless if the online learning concept is not applied in the correct way. This research is aimed to describe qualitatively the instructional design of teaching reading online in a small class which consists of 5 students. The method of the research is qualitative research. The data collected by observing the process of learning and documenting the process. The result found that the small numbers of students is the most important aspect to make the instructional design effective. All the students were active in the online learning. The online media used were Google Meet and WhatApps Group (WAG). The Google meet was the substitution of classroom and WAG was the medium to sending the materials. The highest score for the progress test was 92 and the lowest was 78. The score indicates that the instructional design for teaching reading online in the small class is effective. Keywords: teaching Reading, instructional design, small class